In Search of Better Options: An Ethnographic Inquiry of Migrants from Bharse, Gulmi, Nepal - Pun, Lal Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2024)
This is an extended abstract of my doctoral research, which explored the experiences of migrants seeking better opportunities both within their community of origin and beyond. It examined how migrants sought better opportunities in their community of origin and established their social positionality in new cultural contexts while navigating opportunities, challenges, and future aspirations that have received little academic attention. The purpose was to uncover how migrants faced challenges and developed strategies for the future as they pursued better prospects across multiple locations. To understand this phenomenon, four research questions: a) how do migrants experience detachment while maintaining social networks with their community of origin? b) how do they establish their positionality in new communities? c) how do they perceive both opportunities and constraints? and d) how do they develop strategies for the future? were formulated. Drawing on relevant literature, I used structuration and social capital theories to interpret the stories of migrants from Bharse who have settled in Butwal, Kathmandu, Hong Kong, and London. I employed an ethnographic approach within the interpretative paradigm. The findings indicated that, whether in their community of origin or destination, migrants consistently seek better options for an improved life. My research results will be useful to researchers, policymakers, think tanks, students, and academics who are focused on migration issues.